A new genus and new species of Hymenosomatidae (Crustacea: Brachyura) from Indonesian Papua - Ng, Peter K. L.; Rahayu, Dwi Listyo (Zootaxa, 2022)
A new hymenosomatid crab, Chartocinus rarus n. gen. n. sp., is described from coastal waters in western Papua (formerly Irian Jaya) in Indonesia. The new genus superficially resembles Amarinus Lucas, 1980, but can easily be distinguished by its subquadrate third maxillipeds with the merus produced along the anteroexternal edge, elongate ambulatory legs, elongate male thoracic sternum, short male pleon without distinct intercalated plates on somite 5, and a short male first gonopod in which the inner margin is distinctly bilobed.